2002
DOI: 10.1086/341023
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Procalcitonin Level Accurately Predicts the Absence of Bacteremia in Adult Patients with Acute Fever

Abstract: The ability of measurement of serum procalcitonin (PCT) levels to differentiate bacteremic from nonbacteremic infectious episodes in patients hospitalized for community-acquired infections was assessed. Serum samples were obtained from adult inpatients with fever to determine the serum PCT level, C-reactive protein (CRP) level, and erythrocyte sedimentation rate (ESR). Of 165 patients, 22 (13%) had bacteremic episodes and 143 (87%) had nonbacteremic episodes. PCT levels, CRP levels, and ESRs were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
101
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(122 citation statements)
references
References 21 publications
16
101
1
4
Order By: Relevance
“…Serum procalcitonin (PCT) level is also helpful for ruling out infection in patients with chronic inflammatory diseases and for distinguishing infections from systemic inflammatory diseases in the initial evaluation of patients presenting with acute fever [6]. The PCT level seems to be a reliable tool for predicting bacteremia in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Serum procalcitonin (PCT) level is also helpful for ruling out infection in patients with chronic inflammatory diseases and for distinguishing infections from systemic inflammatory diseases in the initial evaluation of patients presenting with acute fever [6]. The PCT level seems to be a reliable tool for predicting bacteremia in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Procalcitonin (PCT) has been proposed as a useful diagnostic marker in the emergency department, although PCT may fail to rule out BSI (3,9,10).…”
mentioning
confidence: 99%
“…Therefore, surrogate biomarkers are needed to make the appropriate choice more rapidly. In other studies, some authors have previously shown that in a population with proven sepsis, PCT was significantly higher in patients with bacteremia than in those without proven sepsis [9][10][11]. PCT levels have been shown to distinguish between bacteremia and noninfectious inflammatory states quickly and accurately in critically ill patients [5].…”
Section: Discussionmentioning
confidence: 94%